Circular Migration and the Rights of Migrant Workers in Central and Eastern Europe The EU Promise of a Triple Win Solution - Vankova, Zvezda (IMISCOE Research Series,, 2020)
This open access book adopts a rights-based approach to shed light on the different legal and policy instruments that have been developed to implement circular migration policies in the EU, and their consequences for the rights of migrant workers. It contributes to the understanding of the meaning of this concept in general and in the EU, as well as specifically regarding its Eastern neighborhood. The book provides a comprehensive picture of the formation and implementation of the EU's circular migration approach that has developed through both EU and national instruments, on the basis of comparative case study analysis of Bulgaria and Poland's migration laws and policies. By applying empirical legal research methods, it draws conclusions about the policy outcomes from the implementation of the various migration instruments falling under the circular migration umbrella and shows the consequences for the rights of migrant workers as a result of the application of different policy options. Along with its value to an academic audience, the book can be used by policy makers at the EU, international and national levels, as well as by international organisations and NGOs working in the field of migration law and policy.